齿轮轴类零件工艺决策系统的研究 - 李军利; 葛正浩; 王庆水 (Jixie chuandong)
Based on characteristics of the components information,the principle of process decision-making for gear shaft is discussed.Based on the principle of generating processing methods,the entire processing chain of the characteristics is formed by reverse design feature.It lays a foundation for CAD/CAM information sharing.